Posaconazole for the prophylaxis of invasive aspergillosis in acute myeloid leukemia: Is it still useful outside the clinical trial setting? - Chen, Tsung-Chih (Ther Adv Hematol, 2020)
BACKGROUND: Posaconazole prophylaxis during remission induction chemotherapy not only decreases the incidence of invasive aspergillosis (IA) but also improves the overall survival rate among patients with acute myeloid leukemia (AML). However, it remains debatable whether this result applies to patients in a real-world setting. METHODS: We retrospectively assessed 208 adult patients with newly diagnosed AML who underwent remission induction therapy. These 208 patients were stratified into the posaconazole prophylaxis group (n = 58) and no antifungal prophylaxis group (n = 150). RESULTS: Multivariate analyses showed that induction failure significantly increased the risk of proven or probable IA during the first induction chemotherapy [hazard ratio (HR), 10.47; 95% confidence interval (CI), 1.73–63.45; p = 0.011] and the entire course of AML treatment (HR, 4.48; 95% CI, 1.71–11.75; p = 0.002). However, posaconazole prophylaxis did not reduce the risk of IA during the first induction chemotherapy (HR, 1.47; 95% CI, 0.14–15.04; p = 0.746) and during the entire course of AML treatment (HR, 1.09; 95% CI, 0.29–4.09; p = 0.896). Furthermore, there was no significant difference in overall survival between these two groups of patients (514 versus 689 days; p = 0.454). CONCLUSION: Successful induction remains fundamental to reducing the risk of IA among AML patients undergoing remission induction chemotherapy.